Energy and Power for Development by Manas Chatterjee - Planning Commission (Planning Commission, 1971)
One of the major determinants of material progress or development is the productivity of labour force. This is greatly influenced by the quantum of energy incorporated in the productive process. Productivity in any activity is a direct function of the amount of energy used in the process as also the form in which it is used. Functionally, energy has three roles to play: one as a factor of production, the other as a process feed-stock and the third as a consumer item. Hence energy is not only a component of the productive process but also an element fundamental to welfare. An increasing supply of energy per capita is indispensable for all kinds of economic activities encompassing a multitude of productive processes, transportation of products, as also conditioning the environs of work. A study of the changing pattern of energy development in India in the past two decades, therefore, is an essential pre-requisite to the planning for the current decade as also for the foreseeable future.
Government of India Planning Commission